Struktur dan Kaidah Kebahasaan Teks Berita Pencegahan Bullying Laman detik.com Sebagai Alternatif Sumber Belajar Teks Eksplanasi Siswa SMA - Ramadhani, Fadhila; Siroj, Muhammad Badrus (Universitas Muhammadiyah Magelang, 2026)
This study aims to describe the structure and linguistic rules of explanatory texts containing the social phenomenon of bullying prevention on the detik.com page, detikEdu subchannel, and examine its potential as an alternative learning resource for high school students. The research is limited to news texts with the theme of bullying prevention published in November 2025. This study uses a qualitative descriptive approach with data sources in the form of twelve news texts. Data collection techniques are carried out through recording and literature study techniques, while data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that all news texts analyzed are in accordance with the structure of explanatory texts, namely general statements, explanatory sequences, and interpretations. In addition, these texts also fulfill the linguistic rules of explanatory texts, such as the use of causal and temporal conjunctions, technical terms, and mental verbs. Based on these findings, it can be concluded that news texts on the detik.com page, detikEdu subchannel, have the potential to be used as learning resources for explanatory texts that are actual, contextual, and relevant for high school students.